2020
DOI: 10.21673/anadoluklin.719805
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Pandemisi Sırasında Genel Cerrahi Uygulamalarına Yaklaşım

Abstract: Aralık 2019'da Çin'in Hubei eyaletinin Wuhan kentinde sebebi bilinmeyen pnömoni vakaları ortaya çıktı. Çinli bilim insanlar yaptığı çalışmalar sonucunda bu hastalarda pnomoniye neden olan etkenin 'severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2; daha önce bilinen ismiyle 2019-nCoV)' olduğunu ortaya koydu. Hastalık Şubat 2020'de literatüre Coronavirüs Hastalığı 2019 (COVID-19) olarak geçti. Takip eden zamanlarda hastalık hızlı bir şekilde yayıldı ve 11 Mart 2020'de Dünya Sağlık Örgütü (DSÖ) pandemi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Studies conducted during the pandemic have shown that hospitals are not only places where the treatment of COVID-19 is carried out but are also the most important source for the spread of this disease [3]. As a result, discontinuing elective surgical procedures and reducing the frequency of outpatient follow-ups have been an important step to prevent the spread of the disease during the pandemic [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted during the pandemic have shown that hospitals are not only places where the treatment of COVID-19 is carried out but are also the most important source for the spread of this disease [3]. As a result, discontinuing elective surgical procedures and reducing the frequency of outpatient follow-ups have been an important step to prevent the spread of the disease during the pandemic [2].…”
Section: Discussionmentioning
confidence: 99%
“…For non-COVID-19 patients, in many countries, different branches changed their approaches to diseases for this period in accordance with the respective guidelines. Diagnosis and treatment of diseases affecting the quality of life were 132 postponed to appropriate times in places where the pandemic was seen [2]. Similarly, the number of outpatient clinics in Turkish hospitals has been reduced, elective operations have been postponed, and cancer screening has been restricted.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis and treatment of conditions that would not be a threat to life and that would affect only quality of life if not treated urgently are postponed to a more appropriate time to reduce the hospital density. There have been several articles published emphasizing the effects of the COVID-19 pandemic on different surgical procedures performed under emergency conditions, and the precautions to be taken (4)(5)(6). However, there has yet been no study examining the extent to which delays in surgery affect human life in cases of AA, as the cause of acute abdomen requiring emergency surgery.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 is not only an infectious pandemic but also a public health problem that causes anxiety and fear in people due to the risk of death (Alimoğlu & Erol, 2020). Because of the fear of transmitting infection during the pandemic process, healthcare workers separate from their family members and homes and live away from their loved ones (Enli Tuncay et al, 2020;Mo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%